The Effects of Readiness Preparation Program for First-Line Nurse Managers at a Secondary Level Hospital - ยืนบุญ, สหัสพร; สิงห์ช่างชัย, เพชรน้อย; ฉัตรดอกไม้ไพร, กรรณิการ์ (Nursing Journal CMU, 2019)
The objective of this quasi-experimental research was to compare levels of knowledge about qualification requirements and perception of self-efficacy for the position of first line nurse manager between the experimental group and the control group.The sample size was determined using the power of a test, and purposive sampling as employed to recruit 50 nurses that was divided into two groups: 25 for the experimental group and 25 for the control group. The research instruments consisted of a readiness preparation program for the position of first line nurse manager, a knowledge test, and a perceived self-efficacy questionnaire. Content validity of the instrument was 0.93; the KR-21coefficient of the knowledge test was 0.84; and the Cronbach’s alpha coefficient for the perceived self-efficacy questionnaire was 0.94; paired t-test and independent t-test were used. The study found that after the readiness preparation program the experimental group had a very high level of knowledge about qualification requirements for the position of first-line nurse manager (x̄= 12.88, SD = 1.59) while the control group had a moderate level of the knowledge (x̄= 4.80, SD = 1.32) It was also found that the experimental group had significantly more knowledge (p<.05) than the control group. For perceived self-efficacy, the experimental group also had a significantly higher average score (p<.05) than the control group. The results of the study indicated that the readiness preparation program enabled the experimental group to have more knowledge and understanding of career development than the control group, especially in terms of confidence in self-efficacy, engagement at work, outcome expectations, and solving problems by themselves. Thus, the implications of the study are that nursing organizations should organize a standardized readiness preparation course for the position of first line nurse managers that can be used by any nursing organization to prepare nurses to have self-efficacy ready to be first line nurse managers.